The Buddhist Hell: An Early Instance of the Idea? - Braarvig, Jens (Numen, 2009)
In spite of the modern idea that Buddhism is too rational a religion to have a conception of hell, the case is just the opposite. The Buddhists promoted this idea very early. This is not really surprising, since the idea of hell is closely connected with the concept of